Anterior Ethmoidal Nerve Block In Prevention of Post-Operative Agitation Following Nasal Surgeries with Nasal Packs Under General Anesthesia: An Experimental Study - Acharya, Anup; Sharma, Nil Raj; Pokhrel, Bandana; Badtaula, Suman (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Postoperative agitation or emergence agitation during recovery from anesthesia is an important complication of General Anesthesia (GA) especially in otolaryngological surgeries, and nasal surgery in particular. It is potentially harmful to the patients resulting in fall from the operation table, self-extubation, self-removal of nasal pack, hemorrhage etc. Several methods and medications have been tried to reduce it. We studied the effect of anterior ethmoidal nerve block for reducing post-operative agitation for nasal surgeries with nasal packs as it falls in the same operative field. MATERIAL AND METHODS A total of 100 participants undergoing nasal surgeries with nasal pack under GA in the Department of Otolaryngology, Lumbini Medical College, Palpa, Nepal, were randomized into cases and controls by block randomization. The study was done from June 2018 till February 2020. Anterior ethmoidal nerve was blocked with lidocaine injection at the end of surgery in cases. Controls were injected with normal saline. Post-operative agitation was studied with Riker Sedation-Agitation Scale (SAS) and was compared between the two groups. RESULTS There were 50 participants in each group. Emergence agitation in cases and controls at extubation, 30 minutes post-extubation and the next morning was present in 32% and 52%, 4% and 18%, and 0 and 2% respectively. SAS score rapidly decreased in 30 minutes after extubation in controls but was still significantly higher than that of cases. CONCLUSION Anterior ethmoidal nerve block was effective in reducing post-operative agitation significantly during emergence in nasal surgeries with nasal packs.